Cholinesterase and Glycation Inhibition Assay of Several Metabolites Obtained from Plant and Fungi - Islam, Rashedul; Adib, Mohiminul; Ahsan, Monira; Rahman, Md Mustafizur; Mazid, Md Abdul (Dhaka University Journal of Pharmaceutical Sciences, 2019)
Cholinesterase inhibition is one of the major strategies to develop better quality anti-Alzheimer’s drug, while inhibition of glycation pathway is a useful therapeutic strategy to treat diabetic complications. This study was designed to evaluate the anti-acetylcholinesterase, anti-butyrylcholinesterase and anti-glycation activities of 8 secondary metabolites namely, RS-8, RS-22C (arborinine), CL-1 (betulinic acid), CL-2 (ursolic acid), CCL-1 (cajaninstilbene acid), CP-1 (beta-sitosterol), HS-1 (anhydrofusarubin) and HS-2 (methylether of fusarubin). It was found that RS-8 and arborinine showed promising activity in inhibiting acetylcholinesterase with IC50 values of 24.40 ± 0.39 and 13.14 ± 0.07, respectively. Anhydrofusarubin and methyl ether of fusarubin exhibited moderate activities with IC50 values of 47.82 ± 0.54 and 44.58 ± 0.8. Arborinine and cajaninstilbene acid potentially inhibited butyrylcholinesterase with IC50 values of 26.34 ± 0.31 and 25.82 ± 0.34, respectively, but other metabolites did not show such inhibitory activities. Inhibition of glycation process was evaluated by bovine serum albumin assay but none of the metabolites significantly inhibited the glycation pathway. Dhaka Univ. J. Pharm. Sci. 18(1): 31-38, 2019 (June)